3D Ordered Mesoporous Bifunctional Oxygen Catalyst for Electrically Rechargeable Zinc–Air Batteries. Issue 20 (4th April 2016) - Park, Moon Gyu; Lee, Dong Un; Seo, Min Ho; Cano, Zachary Paul; Chen, Zhongwei
Abstract : To enhance energy efficiency and durability, a highly active and durable 3D ordered mesoporous cobalt oxide framework has been developed for rechargeable zinc–air batteries. The bifunctional air electrode consisting of 3DOM Co3 O4 having high active surface area and robust structure, results in superior charge and discharge battery voltages, and durable performance for electrically rechargeable zinc–air batteries.